Tantangan Positivisasi Passing Off di Indonesia - Baso, Fatihani; Iswandi; Uke, La Ode Muhammad Iman Abdi Anantomo; H, Redita Septia Sari. (Department of Constitutional Law, Faculty of Law, University of Jember, Indonesia, 2025)
Hingga saat ini, Indonesia belum mengatur mengenai passing off. Padahal jika melihat fakta di lapangan, banyak sekali produk atau jasa yang dipasarkan meniru produk atau jasa lain yang telah terdaftar. Masalah yang akan dibahas adalah bagaimana urgensi pengaturan khusus passing off dalam sistem hukum Merek di Indonesia serta bagaimana dampak ketidakhadiran aturan Passing Off dalam sistem hukum Indonesia dibandingkan dengan sistem Common Law. Penelitian dilakukan dengan pendekatan perundang-undangan yang dikombinasikan dengan pendekatan konseptual. Secara regulasi, Indonesia yang menganut Civil law system belum mengatur mengenai passing off, melainkan hanya mengatur perlindungan terhadap merek yang telah didaftar. Sedangkan pengaturan passing off tidak hanya melindungi merek yang telah terdaftar, akan tetapi juga melindungi merek yang belum terdaftar. Mengenai apakah passing off dapat diberlakukan di Indonesia, hal itu akan sulit karena perbedaan sistem hukum. Passing off merupakan common law sedangkan Indonesia menganut civil law. Sehingga, passing off tidak tepat jika diadopsi dalam Undang-Undang Merek di Indonesia. Kata Kunci : Positivisasi; Passing Off; Hak atas Merek. Until now, Indonesia has not regulated passing off. In fact, if we look at the facts on the ground, there are many products or services that are marketed that imitate other products or services that have been registered. The problem that will be discussed is how urgent the special regulation of passing off is in the Trademark legal system in Indonesia and how the impact of the absence of Passing Off rules in the Indonesian legal system is compared to the Common Law system. The research was conducted using a legislative approach combined with a conceptual approach. In terms of regulation, Indonesia, which adheres to the Civil law system, has not regulated passing off, but only regulates protection for registered brands. Meanwhile, the regulation of passing off not only protects registered brands, but also protects brands that have not been registered. Regarding whether passing off can be implemented in Indonesia, it will be difficult because of the differences in the legal system. Passing off is common law while Indonesia adheres to civil law. Thus, passing off is not appropriate if adopted in the Trademark Law in Indonesia. Keywords: . Positivisation; Passing Off; Trademark Rights.